Etika Komunikasi Dakwah menurut Al-Quran - Anita Ariani (Alhadharah: Jurnal Ilmu Dakwah, 2012)
The Qur'an mentions dakwah as ahsanu qawla, good words and deeds. In such a context, when the mission is communicated by a preacher, then he or she must have good ethics if he or she wants to preach or to communicate with his or her audience. In addition, in delivering the messages preachers should adjust to the circumstances and the environment where they are preaching. Therefore, ethics is very important in the process of propagation and communication activities. Because ethics is the standard values as reference of behaviour. Without a good communication in preaching, one is considered as rude. Therefore, a preacher must first have good ethics and communication.